Animal domestication and behavior [ - Price, Edward O. (Wallingford, Oxfordshire, UK : CABI, 2002)
Synthesizes the knowledge of the process of domestication and how it has affected the behaviour of captive wild and domesticated animals.
Includes bibliographical references (p. 230-282) and index
Keywords: Animal behavior; Domestication